Thrust Characteristics Analysis and Parameter Optimization of Five-Phase U-Shaped Consequent-Pole PMSLM - Xu, Xiaozhuo; Li, Jingzhou; Jiang, Siyuan; Du, Baoyu; Ji, Shengyang (Journal of electrical engineering & technology, 2025)
In order to improve the thrust characteristics of the multi-phase permanent magnet synchronous linear motor, the five-phase U-shaped consequent-pole permanent magnet synchronous linear motor (FUCP-PMSLM) with 15-slot 16-pole is taken as the research object to analyze the motor thrust and optimize the design parameters. Firstly, the equivalent magnetic circuit method is used to compare the air gap flux density of the U-shaped permanent magnet motor with the non-salient permanent magnet motor, and the influence of the motor phase number changes on the motor thrust is analyzed from the perspective of the magnetomotive force. Secondly, the Taguchi method is used for sensitivity analysis, and four sensitive parameters are selected from seven design parameters as optimization variables, the mathematical model between the motor optimization objectives and optimization variables is obtained by response surface methodology fitting, the multi-objective genetic algorithm is used to solve the problem. The finite element simulation results show that, compared with the initial motor, the average thrust of the optimized motor is increased by 5.8% and the thrust ripple is decreased by 71.3%. Finally, an experimental prototype is fabricated and tested, the test results are basically consistent with the simulation results, which verifies the effectiveness of the design parameter optimization.